Prescribing Practices of Medical Practitioner: A Survey Of Public & Private Sector Registered Medical Practitioner - Garg, Rahul; H, Prasad; J, Singhvi I. (Asian Journal of Pharmaceutical Research and Development, 2013)
To compare various aspects of prescribing behaviors of Medical Practitioner of public and private Sector registered medical practitioners. A pilot survey was conducted for a period of 2 months for Government and private hospital of Udaipur district. After doing a pilot survey of physicians, major factors influencing their peer prescription behavior were found. Quality of medicines is most important for physicians, as it is not only helps curing the disease but also helps in building their reputation. Physicians on the basis of company image and consistent results with a product, judge the quality of products. So company image is also on high priority in their mind while prescribing medicines.A regular visit by a smart, dedicated, well groom having soft skills medical representatives is the best tool of promotion for a pharmaceutical company. Presenting good quality literature, journals and sponsorship for conferences or personal tours are preferable promotional tools in comparison to organization of free camps, personal gifts, medicine samples or any other incentive. It is vital that sales professionals become involved in the process doctors must go through in order to change their clinical behaviours and prescribing habits. If the information a representative has to offer is presented to the physician as an opportunity for learning and improving the problem-solving process, everyone benefits – the doctor, the patients and the representative. By training representative to view time with a doctor as a part of a larger educational process, you make it possible for them to contribute to that learning process and meet their goals more quickly. Scientific information is more effective when used as an educational tool rather than a sales tool